The Utilization of Medical Mask Waste as a High-Quality Nanofiber Material a Review - Victory, Shelly; Putri, Restani Eka; Sakhila, Shania; Hutagalung, Soluna Desbait; Amelia, Addela; Fabiani, Verry Andre (Indonesian Journal of Chemical Science, 2021)
Medical mask waste is part of the covid waste that can threaten the living creatures and environment since it was pathogenic and indestructible. Moreover, the waste management of medical mask waste is still ineffective due to the limit of technology and resource. The purpose of this review is to learn the potency of medical mask waste as the main component of nanofiber fabrication. This review is using the literature review method. There are some fundamental stages for creating nanofiber from polypropylene of medical mask waste, such as pre-treatment, making polypropylene solution, fabrication, and characterization. Removal of medical mask waste contaminants can be using a chemical solvent, dry heat, or exposure to ultraviolet C. Type of solvent plays a principal role in producing polypropylene solvent that is ready to fabricate. On the industrial scale, electrospinning is a commonly used method for nanofiber fabrication. The characterization of the fiber and pore size can be analyzed with scanning electron microscope (SEM) analysis, material crystallinity using x-ray diffraction (XRD) spectroscopy, and thermogravimetric analysis (TGA) measuring the thermal stability of nanofiber.